A TLR7/8 Agonist-Including DOEPC-Based Cationic Liposome Formulation Mediates Its Adjuvanticity Through the Sustained Recruitment of Highly Activated Monocytes in a Type I IFN-Independent but NF-κB-Dependent Manner - Auderset, Floriane; Belnoue, Elodie; Mastelic-Gavillet, Beatris; Lambert, Paul-Henri; Siegrist, Claire-Anne (Frontiers in Immunology, 2020)
Novel adjuvants, such as Toll-like receptors (TLRs) agonists, are needed for the development of new formulations able to circumvent limitations of current vaccines. Among TLRs, TLR7/8 agonists represent promising candidates, as they are well described to enhance antigen-specific antibody responses and skew immunity towards T helper (TH) 1 responses. We find here that the incorporation of a TLR7/8 ligand in a cationic liposome formulation shifts immunity towards TH1 responses and elicits strong and long-lasting germinal center and follicular T helper cell responses in adult mice. This reflects the prolonged recruitment of innate cells towards the site of immunization and homing of activated antigen-loaded monocytes and monocyte-derived dendritic cells towards draining lymph nodes. We further show that this adjuvanticity is independent of type I IFN- but NF-κB-dependent. Overall, our data identify TLR7/8 agonists incorporated in liposomes as promising and effective adjuvants to enhance TH1 and germinal center responses.